Risk for oral cancer from smokeless tobacco - Janbaz, Khalid Hussain; Qadir, M. Imran; Basser, Hibba Tul; Bokhari, Tanveer Hussain; Ahmad, Bashir (Contemporary Oncology/Współczesna Onkologia, 2014)
Tobacco products which are used in a way other than smoking are known as smokeless tobacco. The most common smokeless tobaccos are chewing tobacco, naswar, snuff, snus, gutka, and topical tobacco paste. Any product which contains tobacco is not safe for human health. There are more than twenty-five compounds in smokeless tobacco which have cancer causing activity. Use of smokeless tobacco has been linked with risk of oral cancer. Smokeless tobacco contains tobacco-specific nitrosamines (TSNAs), polonium, formaldehyde, cadmium, lead, and benzo[a]pyrene, which are carcinogenic agents. Although there is presence of some compounds, carotenoids and phenolic compounds, that have cancer inhibiting properties, they are in low concentrations. Dry snuff use is linked with higher relative risks, while the use of other smokeless tobacco is of intermediate risk. Moist snuff and chewing tobacco have a very low risk for oral cancer. Therefore, from this review article, it was concluded that smokeless tobacco has risk for oral cancer – either low, medium or high depending on the balance between cancer causing agents and cancer inhibiting agents.